Endoscopic ultrasound-guided needle-based confocal laser endomicroscopy for diagnosis of gastric subepithelial tumors: a pilot study - Zhang, Ming-Ming; Zhong, Ning; Wang, Xiao; Li, Chang-Qing; Ji, Rui; Li, Zhen; Gu, Xiang; Yu, Yan-Bo; Li, Li-Xiang; Zuo, Xiu-Li; Li, Yan-Qing (Endoscopy, 2019)
Background The diagnostic yield of current techniques for gastric subepithelial tumors (SETs) is suboptimal. This prospective study aimed to develop diagnostic criteria for needle-based confocal laser endomicroscopy (nCLE) of gastric SETs, and to evaluate the diagnostic efficacy, feasibility, and safety of endoscopic ultrasound-guided nCLE (EUS-nCLE).Methods Eligible patients were prospectively recruited to undergo EUS-nCLE. Four unblinded investigators evaluated nCLE videos and corresponding histopathology to develop the nCLE criteria. The recorded nCLE videos were reviewed off-line by one endoscopist 3 months later. Image quality (five-point scale, 1 = poor and 5 = very good) and the interobserver agreements were assessed.Results All 33 patients underwent successful EUS-nCLE procedures. The nCLE criteria for gastric SETs were established. Overall accuracy of off-line nCLE was significantly higher than that of EUS alone (87.9 % vs. 63.6 %; P = 0.02). The mean image quality score was 3.9. The kappa values of the interobserver agreements were 0.66 for gastrointestinal stromal tumor, 0.89 for ectopic pancreas, 0.58 for leiomyoma, and 0.72 for carcinoma.Conclusions EUS-nCLE was feasible and safe to accurately diagnose gastric SETs.